Data from: Moose browsing alters tree diversity effects on birch growth and insect herbivory - Muiruri, Evalyne W.; Milligan, Harriet T.; Morath, Simon; Koricheva, Julia (Dryad, 2015)
Muiruri et al._FunEcol_DRYAD DATAMuiruri et al._DRYAD DATA.xlsx Producer diversity is known to affect a wide range of ecosystem processes including plant growth and insect pest resistance. Consumers such as mammalian herbivores too have been shown to modify plant growth and insect herbivory by triggering changes in host plants. However, few studies have investigated whether consumer effects interact with plant species diversity effects on a focal plant. To unravel consumer-diversity interactions, we recorded both the presence and intensity of winter browsing by moose (Alces alces) on silver birch (Betula pendula) in a long-term forest diversity experiment in Finland and measured birch tree growth as well as insect chewing damage during the following growing season. Although browsing on birch by moose was not affected by tree species richness, the intensity of moose damage altered tree diversity effects on birch tree growth. At minor browsing intensity, tree height, trunk diameter and canopy projections showed positively-humped relationships with tree diversity, peaking at 3-species mixtures. Growth of moderately browsed trees increased with tree species richness, but growth of severely browsed birch trees was unaffected. Moose browsing also altered the direction of tree diversity effects on insect herbivory on birch. Unbrowsed trees experienced lower insect chewing damage in mixed stands (associational resistance) whilst browsed trees suffered more insect chewing damage in diverse stands (associational susceptibility). Increasing browsing intensity also reversed the relationship between tree species richness and insect chewing damage from negative to positive. The observed interactions between moose browsing and tree species richness effects could be explained by lower canopy cover of more diverse stands compared to birch monocultures, leading to increased re-growth capacity and more high-quality foliage of browsed birch trees in more open diverse stands. Our findings demonstrate that both the presence and ...